Porous nanostructured InP: technology, properties, application - Arsentyev, I. N.; Bobyl, A.B.; Konnikov, S.G.; Tarasov, I.S.; Ulin, V.P; Shishkov, M.V.; Boltovets, N.S.; Ivanov, V.N.; Belyaev, A.E.; Konakova, R.V.; Kudryk, Ya.Ya.; Kamalov, A.B.; et al. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
We prepared porous InP (100) substrates with a nanostructured surface relief on which InP epitaxial films were grown. The structure, morphological, and photoluminescence properties of nanostructured substrates and InP epilayers grown on them were studied. These InP epilayers grown on the porous and standard InP substrates were used to make microwave diodes. We showed the advantages of the diodes made on the porous substrates (over those made on the standard ones) caused by higher structural perfection of the InP epilayers grown on the porous substrates.